Community Health Workers as Agents of Health Promotion: Analyzing Thailand’s Village Health Volunteer Program - S. D. Kowitt (2018)
© 2015, Springer Science+Business Media New York. The village health volunteers (VHVs) have been a regular part of Thailand’s health system since the 1960s. Despite widespread recognition, little research has been conducted to describe VHV activities, the settings in which VHVs provide help, how the program is administered, and how changing politics and health problems in Thailand have influenced the program. In order to understand the roles and practices of the VHVs, we conducted in-depth semi-structured interviews and focus groups with VHVs, community leaders and members, and public health officials in three semi-urban communities in central Thailand. Using the Social Ecological Framework, we mapped factors that influenced how the VHVs provided support, including governmental oversight, collaboration with public health officials, and community trust. These influences are discussed as “points of consideration,” which help to identify the strengths and tensions within the VHV program and best practices in supporting and assessing community health worker efforts.